Tracing the Substantive Structure of Historical Knowledge in South African School Textbooks (Yesterday & Today Journal for History Education in South Africa and abroad, 2023)
This article argues that complex substantive knowledge in South African school history textbooks may challenge learners who struggle with reading and comprehension. While debates continue about the balance of substantive and procedural knowledge, both fundamental elements of history knowledge (Lee, 2004), this study employs a qualitative analysis of the substantive content within a Bernsteinian framework. Seven purposively sampled history textbooks, covering grade 3 to grade 9, across the foundation, intermediate, and senior phases of the South African school curriculum are analysed using Maton’s (2013) language descriptions of context and semantics as conceptual tools. Additionally, nominalisation techniques (Coffin, 2006) are used to examine language in the text. Findings indicate significant growth in substantive knowledge manifesting through time, space, context, and semantics.1 Substantive knowledge shifts from a rudimentary and contextualised nature to a more abstract and dense form, including domain-specific conceptual knowledge. Advancing grades produce decontextualised knowledge with heightened semantic density. Increased events under study accompany greater participant diversity. A History student working with these materials would need to be highly proficient in language skills and also capable of processing substantial volumes of abstract content knowledge. Alarming statistics from the Progress in International Reading Literacy Study (Department of Basic Education, 2023) reveal that 81% of grade 4 learners struggle with comprehension in any language, ranking South Africa at the bottom of 57 countries. It is likely that learners would encounter difficulties with the substantive knowledge evident in these textbooks.
Keywords: Content analysis; Contextualization; History knowledge; Proficiency; Semantic shifts; Textbooks